The impact of prison type on prisoners’ aggression and mental health in greek prisons - Μπαμπάσικας Κωνσταντίνος (Psychology: the Journal of the Hellenic Psychological Society, 2017)
Prisons differ in the degree of autonomy they provide to inmates. The objective of this study is to measure the impact of the prison environment, as reflected in the prison types, on prisoners’ self-reported aggression and mental health. This question becomes even more relevant since the recent bill opposing the set-up of a Type-C maximum security prison in Greece. The hypothesis is that the greater the degree of "security" (i.e., closed and judicial prisons being of a higher level of security compared with rural), the more likely the prisoners will be to exhibit aggression or poorer mental health. To test this hypothesis, a Multivariate Analysis of Covariance was used with prisoners’ age and imprisonment years as covariates. Prison type had a statistically significant effect on hostility and verbal aggression (with the highest levels recorded in the judicial prisons) and on depression (with lower levels in the rural prisons). In contrast, the effect of prison type on anger-physical aggression and anxiety was not significant. The results underline the importance of the prison environment and the need for further strengthening of the rural prisons that will help minimize the physical and psychological risks for the inmates.